COMPARATIVE CHARACTERISTICS OF THE GEOLOGICAL STRUCTURE AND LEAD-ZINC MINERALIZATION OF THE USPENSKY (CENTRAL KAZAKHSTAN) AND BEREGIVSKY (TRANSCARPATHIAN) ORE REGIONS - MYKHAILOV, Volodymyr; YESSENDOSSOVA, Ainel (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the article is to conduct a comparative description of the Uspensky in Central Kazakhstan and Beregivsky in Transcarpathian ore regions in order to clarify the factors and criteria for lead-zinc mineralization, patterns of location, formation and localization of polymetallic deposits. The study used general geological methods of research, in particular, methods of geological survey, prospecting and exploration of deposits, a comparative analysis of areas with different geological structures, etc. As a result, it was found that the main factors of polymetallic mineralization are structural, lithological-stratigraphic, magmatic and metasomatic, manifested at different levels of organization of ore matter, at different times, in different geological and structural conditions. The scientific novelty lies in the fact that the conducted studies allow us to recommend the findings regarding the factors and criteria of polymetallic mineralization as scientific and methodological foundations for forecasting and prospecting for leadzinc deposits in other regions of the world, including Ukraine. The practical significance lies in the fact that the new data obtained on the Atasu type of deposits in Kazakhstan allow us to successfully solve many issues of the genesis of such polymetallic deposits, show their relationship and patterns of formation in connection with submarine volcanic activity. These data, in their significance, undoubtedly go far beyond the limits of the Uspensky belt and Central Kazakhstan and are close to other materials of polymetallic deposits of the world.
Keywords: polymetallic mineralization; ore region; factors and criteria of mineralization